Passivation contact structure and preparation method thereof, solar cell and photovoltaic module
By using a dielectric layer and doped polysilicon layer in passivation contact solar cells, the doping concentration and oxide distribution of N-type conductive elements are controlled, and the explosive film and parasitic absorption problems of doped polysilicon layer are solved, thereby improving the solar cell Photoelectric conversion efficiency.
Patent Information
- Application Number
- CN202410392275.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-02
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-04-02
AI Technical Summary
The parasitic absorption and film explosion phenomenon of doped polysilicon layer in existing passivation contact solar cells are mutually restricted, making it difficult to optimize at the same time, affecting the photoelectric conversion efficiency.
A dielectric layer and a doped polysilicon layer doped with N-type conductive elements are used to control the doping concentration of N-type conductive elements and the presence of oxides, so as to inhibit the diffusion and bonding of N-type conductive elements, and reduce the explosive film and parasitic absorption.
It effectively reduces the film explosion phenomenon and parasitic absorption of doped polysilicon layer, and improves the photoelectric conversion efficiency of solar cells.
Smart Images

Figure CN119300548A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solar cells, and in particular to a passivation contact structure and a preparation method thereof, a solar cell and a photovoltaic module. Background Art
[0002] Passivated contact solar cells are a type of solar cells based on selective carrier transport, which have high passivation performance and photoelectric conversion efficiency.
[0003] The passivation contact structure of the passivation contact solar cell includes a dielectric layer and a doped polysilicon layer. The doping concentration of the semiconductor conductive element in the doped polysilicon layer will affect both the degree of parasitic absorption of the doped polysilicon layer and the degree of its film burst. This influence makes it difficult to solve the parasitic absorption and film burst of the doped polysilicon layer at the same time, which has an adverse effect on the photoelectric conversion efficiency of the solar cell. Summary of the invention
[0004] The embodiments of the present invention disclose a passivation contact structure and a preparation method thereof, a solar cell, and a photovoltaic module to solve the problem in the prior art that parasitic absorption and film explosion of a doped polysilicon layer restrict each other and are difficult to be optimized and improved at the same time.
[0005] In a first aspect, an embodiment of the present application discloses a passivation contact structure, the passivation contact structure comprising:
[0006] dielectric layer;
[0007] A doped polysilicon layer doped with an N-type conductive element, wherein the doped polysilicon layer is disposed on the dielectric layer, the doped polysilicon layer comprises an oxide of the N-type doping element, and the doping concentration of the N-type conductive element in the doped polysilicon layer is 1×10 20 cm -3 ~3×10 22 cm -3 , the distribution amount of the N-type conductive element in the doped polysilicon layer presents a decreasing distribution from the side of the doped polysilicon layer away from the dielectric layer to the side of the doped polysilicon layer close to the dielectric layer.
[0008] Furthermore, in the doped polysilicon layer, there is an enriched region of the N-type conductive element, the enriched region is located on a side of the doped polysilicon layer away from the dielectric layer, and the N-type conductive element in the enriched region includes the oxide, which is a phosphorus oxide compound.
[0009] Furthermore, the atomic percentage of the N-type conductive element in the doped polysilicon layer is 5% to 25%.
[0010] Furthermore, the surface doping concentration of the doped polysilicon layer is 2×1020 cm -2 ~8×10 20 cm -2 The junction depth is 0.05μm~0.16μm, and the square resistance is 30Ω / sq~90Ω / sq.
[0011] Furthermore, the thickness of the dielectric layer is 1 nm to 3 nm; and / or,
[0012] The thickness of the doped polysilicon layer is 100nm-120nm.
[0013] In a second aspect, an embodiment of the present application discloses a method for preparing the passivation contact structure according to the first aspect, the preparation method comprising the following steps:
[0014] Providing a silicon substrate, wherein the dielectric layer and the doped amorphous silicon layer doped with the N-type conductive element are sequentially arranged on the surface of the silicon substrate from the inside to the outside;
[0015] Firstly, introducing an oxygen-containing gas into the doped amorphous silicon layer, and then depositing an oxygen-containing layer;
[0016] Annealing is performed to transform the doped amorphous silicon layer into the doped polysilicon layer, and the oxygen-containing gas, the oxygen element in the oxygen-containing layer and the N-type conductive element are combined to form the oxide to inhibit the N-type conductive element in the doped polysilicon layer from diffusing toward the dielectric layer.
[0017] Furthermore, the amount of oxygen-containing gas introduced is greater than or equal to 1000 sccm.
[0018] Furthermore, the thickness of the oxygen-containing layer is 0.5 nm to 50 nm.
[0019] Further, the oxygen-containing gas is deposited by a plasma enhanced chemical vapor deposition process, and the oxygen-containing gas includes at least one of N2O and O2; and / or,
[0020] The oxygen-containing layer is deposited by the plasma enhanced chemical vapor deposition process, and the deposited gas includes SiH4 and the oxygen-containing gas.
[0021] Furthermore, the dielectric layer is deposited by a plasma enhanced chemical vapor deposition process, the deposition temperature is 400° C. to 500° C., and the deposition gas includes the oxygen-containing gas and an inert gas.
[0022] Furthermore, the step of depositing the doped amorphous silicon layer includes first depositing a hydrogenated intrinsic silicon layer and then depositing the doped layer, and the mass content of hydrogen in the intrinsic silicon layer is 10% to 20%.
[0023] Further, the intrinsic silicon layer is deposited by plasma enhanced chemical vapor deposition, the deposition temperature is 400° C. to 500° C., and the deposition gas includes SiH4 and H2;
[0024] The doping layer is deposited by plasma enhanced chemical vapor deposition, and the deposited gas includes SiH4, a gas containing an N-type conductive element, and H2. The gas source flow rate of the gas containing the N-type conductive element is greater than 400 sccm.
[0025] Furthermore, the junction depth of the doping layer is 0.01 μm to 0.1 μm.
[0026] Furthermore, the thickness of the intrinsic silicon layer is 30 nm to 40 nm, and / or,
[0027] The thickness of the doping layer is 70nm-80nm.
[0028] Furthermore, in the annealing process, the annealing temperature is 900°C to 950°C.
[0029] In a third aspect, an embodiment of the present application discloses a solar cell, comprising: the passivation contact structure as described in the first aspect or the passivation contact structure prepared by the preparation method of the passivation contact structure as described in the second aspect.
[0030] In a fourth aspect, an embodiment of the present application discloses a photovoltaic module, comprising: the passivation contact structure as described in the first aspect or the passivation contact structure prepared by the preparation method of the passivation contact structure as described in the second aspect.
[0031] Compared with the prior art, the beneficial effects of this application are:
[0032] The present application provides a passivation contact structure, which includes a dielectric layer and a doped polysilicon layer doped with an N-type conductive element. By controlling the doping concentration of the N-type conductive element in the doped polysilicon layer to 1×10 20 cm -3 ~3×10 22 cm -3, which is conducive to solving the problem of film explosion of the doped polysilicon layer, but at the same time increases the parasitic absorption of the doped polysilicon layer. The doped polysilicon layer includes oxides of N-type conductive elements. The presence of oxides inhibits the diffusion of the internal N-type conductive elements to the dielectric layer side, so that the distribution of the N-type conductive elements from the doped polysilicon layer away from the dielectric layer to the doped polysilicon layer close to the dielectric layer in the doped polysilicon layer shows a downward trend. In other words, by increasing the doping concentration, the phenomenon of film explosion of the doped polysilicon layer can be effectively reduced. Since the existence of N-type conductive elements includes oxides, the degree of parasitic absorption of the doped polysilicon layer caused by high-concentration doping is effectively reduced, so that the problems of film explosion and parasitic absorption of the doped polysilicon layer can be solved at the same time, thereby improving the photoelectric conversion efficiency of solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 is a schematic diagram of the structure of the backlight surface of a solar cell provided in an embodiment of the present application;
[0035] Figure 2 This is a schematic diagram of a structure of an oxygen-containing layer deposited on the backlight surface of a solar cell provided in an embodiment of the present application;
[0036] Figure 3 This is a schematic diagram of a structure of a doped amorphous silicon layer deposited on the backlight surface of a solar cell provided in an embodiment of the present application;
[0037] Figure 4 This is a schematic diagram of another structure of depositing an intrinsic silicon layer and a doped polysilicon layer on the backlight surface of a solar cell provided in an embodiment of the present application;
[0038] Figure 5 is a schematic diagram of the structure of a solar cell provided in an embodiment of the present application;
[0039] Figure 6 is a concentration distribution diagram of silicon, oxygen, and phosphorus elements in a doped polysilicon layer provided in Example 1 of the present application;
[0040] Figure 7 This is the element distribution diagram of phosphorus in the doped polysilicon layer provided in Example 1 of the present application.
[0041] Icons: 1. Silicon substrate; 2. Dielectric layer; 3. Doped polysilicon layer (doped amorphous silicon layer); 31. Intrinsic silicon layer; 32. Doped layer; 4. Oxygen-containing layer; 5. Second functional layer; 6. Diffusion layer; 7. First passivation layer; 8. First anti-reflection layer; 9. First electrode; 10. Second electrode. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] In the present invention, the directions or positional relationships indicated by the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "middle", "vertical", "horizontal", "lateral", "longitudinal" and the like are based on the directions or positional relationships shown in the drawings. These terms are mainly used to better describe the present invention and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific direction, or to be constructed and operated in a specific direction.
[0044] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those skilled in the art, the specific meanings of these terms in the present invention can be understood according to specific circumstances.
[0045] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.
[0046] The technical solution provided by the present invention will be further described below in conjunction with embodiments and drawings.
[0047] Passivated contact solar cells form a thin dielectric layer on the backlight side of the silicon wafer and prepare a doped polysilicon layer on the dielectric layer. The two together constitute the core of the passivated contact solar cell. When preparing the doped amorphous silicon layer, since the deposited film contains a lot of hydrogen elements, when the doped amorphous silicon layer is converted into a doped polysilicon layer during the subsequent annealing process, these hydrogen elements will escape due to the high temperature. The escaped hydrogen gathers to form bubbles and airflow, which will destroy the deposited film layer, which is the so-called "film explosion" phenomenon. This film explosion will destroy the passivation effect of the passivated contact structure and reduce the yield and photoelectric conversion efficiency of the solar cell.
[0048] One way to improve the film burst is to introduce a carbon source into the doped polysilicon layer. The introduction of carbon can form a highly thermally stable CH bond with hydrogen, hindering the escape of H and thus suppressing the film burst phenomenon. However, the introduction of the carbon source increases the contact resistance of the solar cell, which has an adverse effect on the electrical performance. By adjusting the annealing process parameters, reducing the escape of H can also reduce the degree of film burst of the doped polysilicon layer, but this method cannot effectively suppress the occurrence of the film burst phenomenon. The use of an alloyed passivation contact structure can increase the film density of the doped polysilicon layer, thereby effectively suppressing the degree of H escape and reducing the degree of film burst. However, the film density of this method is too high, which greatly hinders the carrier transmission, thus having an adverse effect on the solar cell.
[0049] In response to the above problems, the present application reduces the adverse effects of film explosion by increasing the doping concentration of N-type conductive elements in the doped polysilicon layer and utilizing the binding effect of N-type conductive elements on H elements. However, it was also found that this approach would lead to a significant increase in the parasitic absorption of the doped polysilicon layer, making it difficult to promote further optimization of solar cell performance. To this end, the present application has found through research that the existence state of N-type conductive elements includes oxides, and the presence of the oxides can both reduce the problem of film explosion in the doped polysilicon layer and reduce the parasitic absorption problem caused by the increased concentration of N-type doping elements.
[0050] The passivation contact structure of the present application is a structural component of the solar cell, so the parts related to the solar cell in the following description all refer to the solar cell including the passivation structure, which illustrates the advantages of the passivation contact structure of the present application in the solar cell.
[0051] In the first aspect, the embodiment of the present application discloses a passivation contact structure, which includes: a dielectric layer; a doped polysilicon layer doped with an N-type conductive element, the doped polysilicon layer is arranged on the dielectric layer, the doped polysilicon layer includes an oxide of the N-type conductive element, and the doping concentration of the N-type conductive element in the doped polysilicon layer is 1×10 20 cm -3 ~3×10 22 cm -3, the distribution amount of the N-type conductive element in the doped polysilicon layer shows a decreasing distribution from the side of the doped polysilicon layer away from the dielectric layer to the side of the doped polysilicon layer close to the dielectric layer.
[0052] The passivation contact structure disclosed in the embodiment of the present application can achieve a doping concentration of N-type conductive elements in the doped polysilicon layer of up to 1×10 20 cm -3 ~3×10 22 cm -3 At this doping concentration, the N-type conductive element combines with the hydrogen element, thereby effectively reducing the film explosion of the doped polysilicon layer caused by "H overflow". However, due to the increase in the doping concentration of the N-type conductive element, the N-type conductive element in the doped polysilicon layer diffuses to a higher degree toward the dielectric layer side, thereby increasing the parasitic absorption of light and having an adverse effect on the photoelectric conversion efficiency of the solar cell.
[0053] To this end, the applicant discovered that since the doped polysilicon layer of the solar cell of the present application includes an oxide, the oxide has an inhibitory effect on the diffusion of N-type conductive elements. Therefore, the distribution amount of N-type conductive elements in the doped polysilicon layer from the side of the doped polysilicon layer away from the dielectric layer to the side of the doped polysilicon layer close to the dielectric layer shows a downward trend, thereby effectively inhibiting the diffusion of N-type conductive elements, improving the parasitic absorption of the doped polysilicon layer, and improving the photoelectric conversion efficiency of the solar cell.
[0054] It is understood that N-type conductive elements include phosphorus, arsenic, etc., and the electrons of such elements are carriers and have negative charge. When the N-type conductive element is preferably phosphorus, the doping effect of the doped polysilicon layer is the best. For example, the doping concentration is 1×10 20 cm -3 , 5×10 21 cm -3 , 3×10 22 cm -3 wait.
[0055] In summary, on the one hand, the present application reduces the degree of film bursting of the doped polysilicon layer by doping a higher content of N-type conductive elements in the doped polysilicon layer; on the other hand, since the existence state of the N-type conductive elements includes oxides, the parasitic absorption problem of light caused by high-concentration doping can be effectively alleviated. Therefore, the present application can simultaneously optimize the film bursting and parasitic absorption problems of the doped polysilicon layer, thereby improving the photoelectric conversion efficiency of solar cells.
[0056] Combination Figure 1 It can be seen that Figure 1 Schematic diagram of the structure of the backlight surface of the solar cell provided in the embodiment of the present application, from the doped polysilicon layer 3 away from the dielectric layer 2 side toward the doped polysilicon layer 3 close to the dielectric layer 2 side (ie Figure 1In the direction from bottom to top in the graph, the distribution amount of N-type conductive elements in the doped polysilicon layer 3 shows a downward trend. This is because the inhibitory effect of the oxide causes the N-type conductive elements to exist in an enriched area, which is located on the side of the doped polysilicon layer 3 away from the dielectric layer 2, and because the content of N-type conductive elements in this area is relatively high, the N-type conductive elements on the side of the doped polysilicon layer 3 close to the dielectric layer show a downward trend. Reduce the degree of diffusion of N-type conductive elements into the dielectric layer 2 to avoid the increase of the interface recombination between the dielectric layer 2 and the doped polysilicon layer 3; reduce the high concentration of N-type conductive elements entering the dielectric layer 2, which has an adverse effect on the pore structure of the dielectric layer 2 and affects the transmission of carriers; and reduce the increase in the density of unsaturated dangling bonds and the aggravation of lattice mismatch caused by excessive N-type conductive elements at the interface of the dielectric layer 2.
[0057] In addition, analysis Figure 1 It can be seen that there is a phosphorus-enriched area in the figure (circled area shown in the figure), and the closer to the dielectric layer 2, the lower the phosphorus content. It can be understood that there are phosphorus oxide compounds in the enriched area, which inhibits the diffusion of N-type conductive elements to the dielectric layer 2, so that there is an enriched area of N-type conductive elements in the doped polysilicon layer 3. The phosphorus element in the phosphorus oxide compound is phosphorus in an inactive state and will not replace the silicon in the doped polysilicon layer 3. Therefore, the inactive phosphorus will not become an active impurity in the atomic lattice structure of crystalline silicon, so it will not cause parasitic absorption problems, which helps to increase the current of the solar cell. In addition, phosphorus oxide compounds also have the advantage of passivating dangling bond defects at the grain boundaries, which improves the photoelectric conversion effect of solar cells.
[0058] Furthermore, the atomic percentage of the N-type conductive element in the doped polysilicon layer is 5% to 25%. When the atomic percentage is 5% to 25%, it means that the doped content of the N-type semiconductor element in the doped polysilicon layer is relatively high, so as to avoid a high degree of film explosion of the doped polysilicon layer caused by a low content, and to avoid a high content of the N-type conductive element, the inhibitory effect of the oxide is not obvious, which affects the parasitic absorption of light. Exemplarily, the atomic percentage is 5%, 10%, 20%, 25%, etc.
[0059] Furthermore, the surface doping concentration of the doped polysilicon layer is 2×10 20 cm -2 ~8×10 20 cm -2 The junction depth is 0.05μm~0.16μm, and the square resistance is 30Ω / sq~90Ω / sq.
[0060] It should be noted that the surface doping concentration of the doped polysilicon layer herein refers to the surface of the doped polysilicon layer close to the oxygen-containing layer.
[0061] The square resistance value is affected by the junction depth and doping concentration. The junction depth affects the absorption of light by the solar cell. When the surface doping concentration, junction depth and square resistance of the doped polysilicon layer are within the above range, the conductivity of the solar cell is high and the filling factor is high, so that the photoelectric conversion rate of the solar cell is high. When the doping concentration is higher than this range, Auger recombination is likely to occur, and the open circuit voltage of the battery decreases. When it is lower than this range, the current lateral resistance increases, the current loss is high, and the migration effect of the carriers is affected; when the junction depth is higher than this range, the junction depth is too deep, and the current collection is reduced. When the junction depth is lower than this range, it is greatly affected by the dirt on the surface of the battery, which in turn affects the open circuit voltage of the battery. In addition, the doping concentration of the N-type conductive element of the doped amorphous silicon layer and the degree of diffusion of the N-type conductive element into the doped polysilicon layer determine the surface doping concentration of the doped polysilicon layer. On the basis of providing a higher concentration of doping, the diffusion inhibition effect of oxygen on the N-type semiconductor element is further used to make the surface doping concentration of the doped polysilicon layer of the present application within the above range. For example, the surface doping concentration is 2×10 20 cm -2 , 4×10 20 cm -2 , 6×10 20 cm -2 , 8×10 20 cm -2 etc.; junction depth is 0.05μm, 0.10μm, 0.13μm, 0.16μm, etc.; square resistance is 30Ω / sq, 40Ω / sq, 60Ω / sq, 90Ω / sq, etc.
[0062] The dielectric layer acts as a barrier for electrons and holes, and can be combined with the doped polysilicon layer to form a passivation contact structure to prevent minority carriers from passing through. The dielectric layer can also function as a pinhole channel, allowing carriers in the solar cell to move freely, and selective passage of majority carriers through heavily doped polysilicon is produced, which is beneficial to reduce the recombination loss of minority carriers. In addition, the dielectric layer can be used as a diffusion barrier to prevent the N-type conductive elements of the doped polysilicon layer from diffusing into the semiconductor substrate.
[0063] It should be noted that when the dielectric layer is combined with the doped polysilicon layer to form a passivation contact structure, the effect of the passivation contact structure is related to the thickness of the dielectric layer and the doped polysilicon layer. When the thickness of the dielectric layer is 1nm to 3nm and the thickness of the doped polysilicon layer is 100nm to 120nm, the solar cell has a good passivation contact effect. When the thickness of the doped polysilicon layer and the dielectric layer meets the above range, it helps to reduce the degree of film explosion. This is because the thicker the doped polysilicon layer, the easier it is to have film explosion during the preparation process. In addition, the thicker the doped polysilicon layer, the greater the degree of parasitic absorption. By way of example, the thickness of the dielectric layer is 1nm, 1.4nm, 1.6nm, 2nm, 3nm, etc.; the thickness of the doped polysilicon layer is 100nm, 110nm, 120nm, etc.
[0064] In a second aspect, the present application discloses a method for preparing the passivation contact structure of the first aspect, and the method for preparing the passivation contact structure comprises:
[0065] Providing a silicon substrate, wherein a dielectric layer and a doped amorphous silicon layer doped with an N-type conductive element are sequentially arranged on the surface of the silicon substrate from the inside to the outside;
[0066] First, an oxygen-containing gas is introduced into the doped amorphous silicon layer, and then an oxygen-containing layer is deposited;
[0067] Annealing is performed to transform the doped amorphous silicon layer into a doped polysilicon layer, and the oxygen-containing gas and the oxygen element in the oxygen-containing layer are combined with the N-type conductive element to form an oxide to inhibit the N-type conductive element in the doped polysilicon layer from diffusing toward the dielectric layer.
[0068] The existence state of the N-type conductive element in the present application includes oxides, and the oxide is formed by introducing an oxygen-containing gas into the doped amorphous silicon layer, then depositing an oxygen-containing layer, and then in the annealing process, while the doped amorphous silicon layer is transformed into a doped polycrystalline silicon layer, the oxygen-containing gas and the oxygen element in the oxygen-containing layer are combined with the N-type conductive element, and the oxide inhibits the diffusion of the N-type conductive element to the dielectric layer. In this process, the oxygen-containing gas is injected into the doped amorphous silicon layer before the oxygen-containing layer is prepared, and after the subsequent annealing process, the oxygen in the oxygen-containing gas is further diffused into the interior of the doped polycrystalline silicon layer, thereby combining with the internal N-type conductive element, inhibiting the internal N-type conductive element from diffusing to the dielectric layer side, and the oxygen in the oxygen-containing layer is combined with the N-type conductive element on the surface of the doped polycrystalline silicon layer under the advancement of annealing, thereby inhibiting the diffusion of the surface N-type conductive element to the interior of the doped polycrystalline silicon layer. That is to say, by combining the oxygen element with the excess N-type conductive element in the doped polysilicon layer in this way, the degree of film explosion of the doped polysilicon layer is reduced, and at the same time, the degree of diffusion of the N-type conductive element to the dielectric layer is effectively reduced, and the probability of the N-type conductive element penetrating the dielectric layer into the silicon substrate is reduced, and the light parasitic absorption is reduced, thereby effectively improving the photoelectric conversion efficiency of the solar cell. In addition, the oxygen-containing layer can also be used as a protective layer to reduce the degree of corrosion of the doped polysilicon layer on the back by the cleaning liquid in the subsequent cleaning step.
[0069] The present application reduces the parasitic absorption of light by, on the one hand, introducing an oxygen-containing gas, which further diffuses into the interior of the doped polycrystalline silicon layer during annealing, thereby combining with the internal phosphorus to inhibit its further internal expansion, and on the other hand, depositing an oxygen-containing layer, wherein the oxygen in the oxygen-containing layer combines with the phosphorus on the surface of the doped polycrystalline silicon layer under the action of annealing, thereby effectively inhibiting the diffusion of the surface phosphorus into the interior. Therefore, the setting of the oxygen-containing gas and the oxygen-containing layer of the present application effectively inhibits the tendency of phosphorus to diffuse toward one side of the dielectric layer, and reduces the degree of parasitic absorption of the doped polycrystalline silicon layer. In addition, although the parasitic absorption problem of light can be improved to a certain extent by not depositing an oxygen-containing layer, but only introducing an oxygen source while depositing the doped amorphous silicon layer (i.e., the prepared doped amorphous silicon layer includes phosphorus and oxygen), the oxygen in this method is randomly distributed in the phosphorus-doped amorphous silicon layer, and it is difficult to control the distribution area of the oxygen source in the doped amorphous silicon layer, resulting in a low oxygen-phosphorus combination rate, which has an adverse effect on the inhibition effect of phosphorus diffusion into the interior.
[0070] From the above analysis, it can be seen that the present application reduces the parasitic absorption of light caused by high-concentration phosphorus doping through the binding effect of oxygen in the oxygen-containing gas and the oxygen-containing layer on phosphorus, thereby simultaneously achieving the optimization of film burst and parasitic absorption of the doped polysilicon layer and improving the photoelectric conversion efficiency of solar cells.
[0071] In the embodiment of the present application, the dielectric layer and the doped polysilicon layer can be arranged on the light-receiving surface of the silicon substrate, or on the backlight surface of the silicon substrate, or on both sides. The following takes the dielectric layer and the doped polysilicon layer arranged on the backlight surface of the silicon substrate as an example for further explanation.
[0072] See also Figure 2 , Figure 2 A schematic diagram of the structure of an oxygen-containing layer deposited on the backlight surface of a solar cell provided in an embodiment of the present application, wherein a dielectric layer 2 and a phosphorus-doped amorphous silicon layer 3 are formed on the backlight surface of a silicon substrate 1 from the inside to the outside, an oxygen-containing gas is introduced into the doped amorphous silicon layer 3, and then an oxygen-containing layer 4 is deposited, and then the doped amorphous silicon layer 3 is transformed into a doped polycrystalline silicon layer 3 through subsequent annealing. In the figure, the content of activated phosphorus close to the dielectric layer 2 is relatively low, indicating that the oxygen element in the oxygen-containing gas and the oxygen-containing layer 4 combines with the phosphorus element to inhibit the phosphorus element in the doped polycrystalline silicon layer 3 from diffusing toward the dielectric layer 2 side.
[0073] In order to ensure that oxygen inhibits the diffusion of N-type conductive elements inside the doped polysilicon layer, the parasitic absorption problem is effectively solved. The flow rate of the oxygen-containing gas is greater than or equal to 1000sccm, preferably in the range of 1000sccm to 8000sccm, and the thickness of the oxygen-containing layer is 0.5nm to 50nm. When the flow rate of the oxygen-containing gas is within the above range and the thickness of the oxygen-containing layer is 0.5nm to 50nm, it is ensured that sufficient oxygen is combined with the N-type conductive elements of the doped polysilicon layer, and the oxygen is promoted in the subsequent annealing process. On the one hand, the oxygen-containing gas reduces the diffusion of excessive phosphorus inside the doped polysilicon layer, and on the other hand, the oxygen-containing layer reduces the diffusion of phosphorus on the surface of the doped polysilicon layer to the inside, thereby reducing the parasitic absorption of the doped polysilicon layer and the probability of phosphorus penetrating the dielectric layer. It also helps to avoid the problem that too high oxygen content leads to poor corrosion resistance of the doped polysilicon layer, increased production costs, and long process time; it also avoids the problem that the oxygen content is too low and the content combined with the N-type semiconductor element is low, which makes it difficult to effectively reduce parasitic absorption. Illustratively, the amount of oxygen-containing gas introduced is 1000 sccm, 5000 sccm, 8000 sccm, 10000 sccm, etc.; the thickness of the oxygen-containing layer is 0.5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, etc.
[0074] The present application may adopt deposition methods such as plasma-enhanced chemical vapor deposition (PECVD) and low pressure chemical vapor deposition (LPCVD). It is preferred to use the PECVD deposition method to deposit the dielectric layer, the doped amorphous silicon layer, the oxygen-containing gas, and the oxygen-containing layer. Compared with the LPCVD method, the PECVD deposition has the advantages of low degree of plating, easy removal of plating, thinner doped amorphous silicon layer, and high deposition efficiency. However, after deposition using such a method, the doped polycrystalline silicon layer is obtained. The high H content easily causes the doped polycrystalline silicon layer to explode, thereby affecting the yield and efficiency of the solar cell. Therefore, the present application increases the doping concentration of the N-type conductive element of the doped polycrystalline silicon layer, and reduces the risk of the doped polycrystalline silicon layer exploding due to H escape through the inhibitory effect of the N-type conductive element on H.
[0075] Furthermore, the annealing temperature is 900°C to 950°C. When the annealing temperature is within the above range, not only the doped amorphous silicon layer is transformed into a doped polysilicon layer, but also the oxygen element is further pushed into the interior of the doped polysilicon layer and combined with the internal N-type conductive element. It is worth noting that if the LPCVD method is used to prepare the doped polysilicon layer, the deposition temperature is 550°C to 600°C, which is higher than the deposition method using PECVD, and the annealing process not only involves the transformation of amorphous silicon into a polysilicon layer, but also involves the process of inward diffusion of N-type conductive elements and forming an activated state, while the annealing of PECVD is mainly the activation of N-type conductive elements and the transformation of amorphous silicon layers into polysilicon layers, and the diffusion of N-type conductive elements is mainly carried out during the deposition process. Compared with LPCVD, the distribution uniformity of N-type conductive elements in the doped polysilicon layer of PECVD is higher.
[0076] The oxygen-containing gas is deposited by PECVD, wherein the deposited oxygen-containing gas includes at least one of N2O and O2. Under the discharge action of PECVD, the oxygen element enters the interior of the doped amorphous silicon layer, so that in the subsequent annealing process, the oxygen element can further diffuse inward and combine with the internal N-type conductive element, thereby reducing the probability of the N-type conductive element penetrating the dielectric layer. In the preparation process of the oxygen-containing layer, the deposited gas includes SiH4 and an oxygen-containing gas, and the specific deposition gas is SiH4, O2, or SiH4, N2O, O2, or SiH4, N2O.
[0077] When depositing the dielectric layer and the doped amorphous silicon layer, the deposition is performed in a negative pressure environment at 400°C to 500°C. When depositing the dielectric layer, the deposited gas includes oxygen-containing gas and inert gas. Under the discharge action of PECVD, the above-mentioned gas is ionized into an ion state, thereby reacting with the silicon wafer to form a dielectric layer, wherein the deposited gas is N2, N2O, O2, or N2, N2O, or N2, O2, etc.
[0078] In a first alternative embodiment, see Figure 3 , Figure 3 The schematic diagram of the structure of a doped amorphous silicon layer deposited on the back side of a solar cell provided in the present application, wherein the doped polycrystalline silicon layer 3 is directly deposited with a doped amorphous silicon layer 3 containing an N-type conductive element, and the doped amorphous silicon layer 3 is directly converted into a doped polycrystalline silicon layer 3 after annealing. In the second optional embodiment, see Figure 4 , Figure 4 A schematic diagram of the structure of another type of solar cell backlight surface deposited with an intrinsic silicon layer and a doped layer is provided in the present application. The doped polysilicon layer 3 is prepared by first preparing an intrinsic silicon layer 31, and then depositing a doped layer 32 containing an N-type conductive element. After annealing, part of the N-type conductive element in the doped layer 32 enters the intrinsic silicon layer 31, so that the doped layer 32 and the intrinsic silicon layer 31 together constitute the doped polysilicon layer 3.
[0079] Among them, in the second optional implementation, the intrinsic silicon layer is a hydrogenated intrinsic silicon layer, and the deposited gases are SiH4 and H2. Under the discharge action of PECVD, the gas is ionized into an ionic state to generate a hydrogenated intrinsic silicon layer; then SiH4, PH3 and auxiliary gas H2 are introduced, and under the discharge action of PECVD, a doped polycrystalline silicon layer is generated, and the amorphous silicon is crystallized through annealing, and the hydrogenated intrinsic silicon layer and the doped layer are transformed into a doped polycrystalline silicon layer together, wherein the mass content of hydrogen element in the intrinsic silicon layer is 10% to 20%.
[0080] A two-step method is used to prepare the doped polysilicon layer, in which the intrinsic silicon layer can be used as a barrier layer, which increases the difficulty of N-type conductive elements diffusing into the dielectric layer, effectively reduces surface recombination, and improves the photoelectric conversion efficiency of solar cells. In addition, since the hydrogen content in the intrinsic silicon layer is within the above range, it not only reduces the risk of film explosion caused by H escape, but also has a passivation effect, which improves the photoelectric conversion efficiency of solar cells, avoids the increase in the degree of film explosion of the doped polysilicon layer caused by excessive H content, and avoids the poor passivation effect of H caused by too low H content, which makes it difficult to optimize the passivation contact structure. Exemplarily, the mass content of hydrogen element is 10%, 14%, 18%, 20%, etc.
[0081] In addition, the thickness of the intrinsic silicon layer prepared in the process is 30nm-40nm, and the thickness of the doped layer is 70nm-80nm. When the thickness of the intrinsic silicon layer and the doped layer is within the above range, the thickness of the doped polysilicon layer prepared is thicker, which is beneficial to improving the passivation effect of the passivation contact structure. The thickness of the intrinsic silicon layer is within the above range, which ensures that the distance of the N-type conductive element to diffuse inward is relatively high, which increases the difficulty of diffusion, thereby helping the oxygen element to inhibit the diffusion of the N-type conductive element and reduce the degree of its diffusion into the dielectric layer. In addition, if the thickness of the intrinsic silicon layer is too low, the distance of the N-type conductive element to diffuse into the dielectric layer is reduced, increasing the probability of its penetration into the dielectric layer. When the thickness is too high, it will affect the effect of the passivation contact and increase the cost of the process. If the thickness of the doped layer is too high, the thickness of the doped polysilicon layer is high, increasing the degree of film explosion. If the thickness of the doped layer is too low, the doping content of the N-type conductive element is low, which is not conducive to improving the passivation contact structure. Exemplarily, the thickness of the intrinsic silicon layer is 30 nm, 35 nm, 40 nm, etc.; the thickness of the doped layer is 70 nm, 75 nm, 80 nm, etc.
[0082] The junction depth of the doping layer is 0.01μm to 0.1μm. Within this range, the doping layer has a better effect on absorbing current. When the junction depth is higher than this range, the junction depth is too deep and the current collection is reduced. When the junction depth is lower than this range, it is greatly affected by the dirt on the battery surface, thereby affecting the open circuit voltage of the battery. Exemplarily, the junction depth of the doping layer is 0.01μm, 0.04μm, 0.06μm, 0.08μm, 0.1μm, etc.
[0083] The passivation contact structure is part of the structure of the solar cell. Before the step of preparing the passivation contact structure, the preparation process of the solar cell includes: texturing the silicon substrate; forming a diffusion layer on the side of the silicon substrate facing away from the dielectric layer, and the diffusion layer forms a wrap-around layer on the dielectric layer side of the silicon substrate and / or the side of the silicon substrate; removing the wrap-around layer and polishing the dielectric layer side of the silicon substrate.
[0084] The purpose of texturing is to remove dirt from the silicon substrate, prepare a velvet surface, and increase the ability to absorb sunlight; the purpose of alkali polishing is to remove excess coating to prevent leakage, reduce its ability to capture carriers, and polish the dielectric layer side of the silicon substrate at the same time, so that the subsequently deposited dielectric layer and doped polysilicon layer have a higher flatness, which is beneficial to reduce the film bursting phenomenon caused by stress concentration during the deposition process.
[0085] After the step of preparing the passivation contact structure, the preparation process of the solar cell includes: cleaning the silicon substrate to remove the oxygen-containing layer; preparing a first functional layer on the side of the diffusion layer away from the silicon substrate, and preparing a second functional layer on the side of the doped polysilicon layer away from the dielectric layer; the first functional layer is a first passivation layer and / or a first anti-reflection layer, and the second functional layer is a second passivation layer and / or a second anti-reflection layer; printing and sintering a first electrode on the first functional layer so that the first electrode penetrates the first functional layer and is in ohmic contact with the diffusion layer, and printing and sintering a second electrode on the second functional layer so that the second electrode penetrates the second functional layer and is in ohmic contact with the doped polysilicon layer.
[0086] It should be noted that in the step of cleaning the silicon substrate, when removing the dielectric layer and the doped polysilicon layer deposition process, the oxygen-containing layer can be used as a protective layer to protect the passivation contact structure of the silicon substrate from being corroded by the cleaning solution. After removing the plating layer, the oxygen-containing layer is further removed, thereby facilitating the subsequent deposition of the second functional layer. Among them, the passivation layer reduces surface recombination and improves the photoelectric conversion efficiency of the solar cell; the presence of the anti-reflection layer can reduce the reflection of the incident light on the one hand, and on the other hand, it can play a passivation role, further improving the photoelectric efficiency of the solar cell. The printing and sintering of the metal electrode allows the electrode to form an ohmic contact with the silicon substrate, improves the open circuit voltage and fill factor of the battery, and improves the photoelectric conversion efficiency of the battery. Exemplarily, the first functional layer is a first passivation layer, a first anti-reflection layer, or a first passivation layer and a first anti-reflection layer; the second functional layer is a second anti-reflection layer, a second passivation layer, or a second passivation layer and a second anti-reflection layer.
[0087] In a third aspect, the present application provides a solar cell, which includes the passivation contact structure of the first aspect, or the passivation contact structure is prepared by the preparation method of the second aspect.
[0088] See also Figure 5 The solar cell of the present application includes a silicon substrate 1, the light-receiving surface of the silicon substrate 1 sequentially comprises a diffusion layer 6, a first passivation layer 7 and a first anti-reflection layer 8, wherein the diffusion layer 6 forms a PN junction with the silicon substrate 1; the backlight surface of the silicon substrate 1 sequentially comprises a dielectric layer 2, a doped polysilicon layer 3 and a second passivation layer 5, in addition, a first electrode 9 is arranged on the surface of the first anti-reflection layer 8, and a second electrode 10 is arranged on the surface of the second passivation layer 5.
[0089] In a fourth aspect, the present application provides a photovoltaic module, which includes the passivation contact structure of the first aspect, or the passivation contact structure is prepared by the preparation method of the second aspect.
[0090] The technical solution of the present application will be further explained below in conjunction with more specific embodiments and experimental test results.
[0091] Embodiment 1:
[0092] The present invention provides a method for preparing a solar cell, which comprises the following steps:
[0093] Texturing the silicon substrate: Texturing the N-type silicon substrate, firstly use 1% alkali solution to texturing, and then use hydrogen peroxide and alkali to clean the silicon substrate;
[0094] The silicon substrate after texturing is placed in a boron diffusion furnace, and is diffused at 1000° C. to 1080° C. using boron trichloride gas to form a diffusion layer on the light-receiving surface of the silicon substrate, and the diffusion layer forms a wrap-around coating on the backlight surface and / or the side of the silicon substrate;
[0095] A chain HF device is used to remove the boron-containing glass on the backlight surface of the silicon substrate due to boron expansion, and then a trough wet process device is used to remove the coating on the backlight surface and side of the silicon substrate, and the backlight surface of the silicon substrate is polished.
[0096] Preparation of passivated contact structure:
[0097] Using PECVD, under negative pressure and temperature of 450°C, a 1nm silicon dioxide dielectric layer and a phosphorus-doped amorphous silicon layer are formed from the inside to the outside on the backlight side of the silicon substrate, wherein the doped amorphous silicon layer includes a 40nm thick hydrogenated intrinsic silicon layer and an 80nm thick doped layer;
[0098] Using PECVD, 1000 sccm of oxygen was first introduced into the doped amorphous silicon layer, and then oxygen and SiH4 were introduced to deposit a 10nm thick oxygen-containing layer;
[0099] Annealing at 900°C transforms the intrinsic silicon layer and the doped layer into a doped polysilicon layer, and combines the oxygen-containing gas and the oxygen element in the oxygen-containing layer with the N-type conductive element to form an oxide to inhibit the N-type conductive element in the doped polysilicon layer from diffusing toward the dielectric layer. The doping concentration of the doped polysilicon layer is 5×10 21 cm -3 , the atomic percentage of phosphorus in the doped polysilicon layer is 15%;
[0100] Using a hydrofluoric acid solution to clean the silicon substrate to remove the oxygen-containing layer;
[0101] A first passivation layer of aluminum oxide and a first anti-reflection layer of silicon nitride are sequentially prepared from the inside to the outside on the side of the diffusion layer away from the silicon substrate, and a second functional layer is prepared on the side of the doped polysilicon layer away from the dielectric layer, wherein the functional layer is a silicon nitride layer having both anti-reflection and passivation effects;
[0102] A first electrode is printed and sintered on the first anti-reflection layer so that the first electrode penetrates the first functional layer and makes ohmic contact with the diffusion layer. A second electrode is printed and sintered on the second functional layer so that the second electrode penetrates the second functional layer and makes ohmic contact with the doped polysilicon layer to produce a solar cell.
[0103] Performance test 1:
[0104] See also Figure 6 , Figure 6 The concentration distribution diagram of silicon, oxygen, and phosphorus in the doped polysilicon layer of the present application shows that a relatively high concentration of oxygen has been observed in the doped polysilicon layer. These oxygens will form phosphorus-oxygen compounds with excess phosphorus, and the phosphorus in the phosphorus-oxygen compounds is in an inactive state, thereby improving the problem of parasitic absorption. At the same time, due to the binding of oxygen, the inward expansion of phosphorus to one side of the dielectric layer is limited, reducing the probability of phosphorus penetrating the dielectric layer and improving the photoelectric conversion efficiency of solar cells.
[0105] See also Figure 7 , Figure 7 This is an element distribution diagram of phosphorus in the doped polysilicon layer after annealing. In the figure, there is an enriched area of phosphorus in the doped polysilicon layer. The existence of this enriched area is mainly due to the inhibitory effect of the oxygen-containing gas on the phosphorus inside the doped polysilicon layer and the inhibitory effect of the oxygen-containing layer on the phosphorus on the surface of the doped polysilicon layer, which makes the phosphorus element of the doped polysilicon layer close to the dielectric layer side show a downward trend, reducing the probability of penetrating the dielectric layer. In addition, the phosphorus in this enriched area is non-activated phosphorus, which does not produce parasitic absorption and will not have an adverse effect on the current of the solar cell.
[0106] Embodiment 2
[0107] The difference between this embodiment and the first embodiment is that the doping concentration of the N-type conductive element in the doped polysilicon layer is 1×10 20 cm -3 .
[0108] Embodiment 3
[0109] The difference between this embodiment and the first embodiment is that the doping concentration of the N-type conductive element in the doped polysilicon layer is 3×10 22 cm -3 .
[0110] Embodiment 4
[0111] The only difference between this embodiment and the first embodiment is that the thickness of the oxygen-containing layer is 5 nm.
[0112] Embodiment 5
[0113] The only difference between this embodiment and the first embodiment is that the thickness of the oxygen-containing layer is 30 nm.
[0114] Embodiment 6
[0115] The only difference between this embodiment and the first embodiment is that the thickness of the oxygen-containing layer is 70 nm.
[0116] Embodiment 7
[0117] The only difference between this embodiment and the first embodiment is that the amount of oxygen-containing gas introduced is 300 sccm.
[0118] Embodiment 8
[0119] The only difference between this embodiment and the first embodiment is that the amount of oxygen-containing gas introduced is 2500 sccm.
[0120] Embodiment 9
[0121] The only difference between this embodiment and the first embodiment is that the thickness of the intrinsic silicon layer is 25 nm.
[0122] Embodiment 10
[0123] The only difference between this embodiment and the first embodiment is that the thickness of the intrinsic silicon layer is 50 nm.
[0124] Embodiment 11
[0125] The only difference between this embodiment and the first embodiment is that the doped polysilicon layer is deposited by LPCVD, and the thickness of the doped polysilicon layer is 100 nm.
[0126] Embodiment 12
[0127] The only difference between this embodiment and the first embodiment is that in the process of preparing the doped polycrystalline silicon layer, there is no need to deposit an intrinsic silicon layer, and a doped amorphous silicon layer with a thickness of 120 nm is directly deposited.
[0128] Comparative Example 1
[0129] The difference between this comparative example and the first embodiment is that no oxygen-containing gas is introduced into the phosphorus-doped amorphous silicon layer, and no oxygen-containing layer is deposited.
[0130] Comparative Example 2
[0131] The difference between this comparative example and the first embodiment is that the oxygen-containing gas is not introduced into the phosphorus-doped amorphous silicon layer, and the oxygen-containing layer is directly deposited on the surface of the phosphorus-doped polycrystalline silicon layer.
[0132] Comparative Example 3
[0133] The difference between this comparative example and the first embodiment is that only the oxygen-containing gas is introduced into the phosphorus-doped amorphous silicon layer, but the oxygen-containing layer is not deposited.
[0134] Comparative Example 4
[0135] The difference between this comparative example and the first embodiment is that the doping concentration of the N-type conductive element in the doped amorphous silicon layer is 5×10 19 cm -3 .
[0136] Comparative Example 5
[0137] The difference between this comparative example and the first embodiment is that the doping concentration of the N-type conductive element in the doped amorphous silicon layer is 1×10 23 cm -3 .
[0138] Performance Test 2:
[0139] Surface doping concentration: tested using electrochemical capacitance-voltage profiler (ECV).
[0140] Junction depth: The electrochemical capacitance-voltage profiler (ECV) is used for testing, and the junction depth is determined by observing the depth corresponding to the concentration inflection point.
[0141] Square resistance: Use a four-probe square resistance tester to test the square resistance.
[0142] Table 1 Performance test results of doped polysilicon layer
[0143]
[0144]
[0145] Analysis of the values of surface doping concentration, junction depth, and square resistance of the embodiments and comparative examples show that the above-mentioned characterization parameters of the embodiments are all within the scope of the present application, while the above-mentioned parameters in the comparative examples are not within the scope of the present application. Therefore, the solar cell prepared in the embodiments has a higher degree of light absorption, a higher conductivity, and a higher fill factor, which helps to improve the photoelectric conversion efficiency of the solar cell.
[0146] Performance Test 3:
[0147] The solar cells prepared in Examples 1 to 12 and Comparative Examples 1 to 5 were subjected to the following related tests:
[0148] The present application provides a solar cell, using the halm test sorting equipment to perform open circuit voltage, short circuit current and fill factor performance tests. The halm machine is a device that simulates sunlight, and is equipped with electronic loads, data acquisition and calculation equipment to test the electrical performance of photovoltaic devices (including solar cells). The silicon wafer of the solar cell under control is 182 in size, and the calibrated light intensity is 1000±5W / m 2 ,The experimental test results are as follows.
[0149] Table 2 Performance test results of solar cells
[0150]
[0151]
[0152] Analysis of the data of Examples 1 to 12 and Comparative Examples 1 to 3 shows that the photoelectric conversion efficiency of the examples is better than that of the comparative examples. This is because during the preparation process, the doped polycrystalline silicon layer in the examples is first introduced with an oxygen-containing gas, and then the oxygen-containing layer is deposited. Therefore, under the action of annealing, the oxygen element in the oxygen-containing gas diffuses into the interior of the doped polycrystalline silicon layer and combines with the phosphorus element, thereby inhibiting the internal expansion of the phosphorus element. The oxygen element in the oxygen-containing layer combines with the phosphorus element on the surface of the doped polycrystalline silicon layer, thereby inhibiting the diffusion of the surface phosphorus element into the doped polycrystalline silicon layer. As a result, the phosphorus element in the doped polycrystalline silicon layer shows a downward trend, reducing the parasitic absorption of the doped polycrystalline silicon layer, and improving the photoelectric conversion efficiency of the solar cell.
[0153] By analyzing the data of Examples 1 to 3 and Comparative Examples 4 and 5, it can be seen that the photoelectric conversion efficiency of the examples is better than that of Comparative Example 4. This is because the doping concentration of the doped polysilicon layer in the examples is higher, which helps to solve the problem of film bursting of the doped polysilicon layer, thereby improving the performance of the solar cell; the data of the examples are better than that of Comparative Example 5. This is because the doping concentration of the examples is lower, so the content of internal diffusion of phosphorus is lower, which improves the light parasitic absorption problem of the doped polysilicon layer and improves the performance of the solar cell.
[0154] By analyzing the data of Example 1 and Example 4 to Example 6, it can be seen that the data of Example 1 and Example 4 to Example 5 are better than those of Example 6. This is because the deposition thickness of the oxygen-containing layer of Examples 1, 4 and 5 is within the preferred range of the present application, thereby avoiding excessively high oxygen content in the doped polysilicon layer due to excessive thickness of the oxygen-containing layer, which makes the stability of the doped polysilicon layer poor and affects the performance of the solar cell.
[0155] Analysis of the data of Example 1, Example 7, and Example 8 shows that the data of Example 1 and Example 8 are better than those of Example 7. This is because the amount of oxygen-containing gas introduced in Example 1 and Example 8 is within the preferred range of the present application, which effectively suppresses the downward expansion of the phosphorus element inside the doped polysilicon layer, solves the problem of light parasitic absorption of the doped polysilicon layer, and improves the quality of the passivation contact, thereby improving the photoelectric conversion efficiency of the solar cell.
[0156] By analyzing the data of Example 1, Example 9 and Example 10, it can be seen that the data of Example 1 is better than that of Example 9. This is because the intrinsic silicon layer of Example 1 is thicker, so it can effectively block the internal expansion of phosphorus elements, thereby improving the problem of light parasitic absorption and improving the photoelectric conversion efficiency of solar cells; the data of Example 1 is better than that of Example 10 because the intrinsic silicon layer of Example 1 is thinner, so it helps to improve the passivation effect of the passivation contact structure, thereby improving the photoelectric conversion efficiency of solar cells.
[0157] Analysis of the data of Example 1 and Example 11 shows that the data of Example 1 is better than that of Example 11. This is because Example 1 adopts the PECVD deposition method to prepare solar cells, wherein PECVD is an in-situ doping preparation method, specifically, silane and phosphine are ionized by plasma discharge, and the doping temperature is low to form an in-situ doped phosphorus-doped amorphous silicon layer, and the introduction of oxygen-containing gas and the deposition of the oxygen-containing layer further reduce the tendency of phosphorus element to expand inward when the doped amorphous silicon layer is transformed into a doped polycrystalline silicon layer, thereby increasing the short-circuit current density and optimizing the photoelectric conversion efficiency of the solar cell. Moreover, the deposition efficiency using this method is higher.
[0158] By analyzing the data of Example 1 and Example 12, it can be seen that the data of Example 1 is better than that of Example 12. This is because in the preparation process of the doped polysilicon layer of Example 1, intrinsic silicon is first prepared and then the doped layer is deposited, wherein the intrinsic silicon layer can be used as a barrier layer, which can increase the difficulty of phosphorus element diffusing to the dielectric layer side, reduce surface recombination, and improve the photoelectric conversion efficiency of the solar cell.
[0159] The above is a detailed introduction to the passivation contact structure and preparation method thereof, solar cells, and photovoltaic modules disclosed in the embodiments of the present application. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions of the embodiments of the present application. At the same time, for those skilled in the art, according to the ideas of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A passivation contact structure, characterized in that: The passivation contact structure comprises: dielectric layer; A doped polysilicon layer doped with an N-type conductive element, wherein the doped polysilicon layer is disposed on the dielectric layer, the doped polysilicon layer comprises an oxide of the N-type conductive element, and the doping concentration of the N-type conductive element in the doped polysilicon layer is 1×10 20 cm -3 ~3×10 22 cm -3 , the distribution amount of the N-type conductive element in the doped polysilicon layer presents a decreasing distribution from the side of the doped polysilicon layer away from the dielectric layer to the side of the doped polysilicon layer close to the dielectric layer.
2. The passivation contact structure according to claim 1, characterized in that: The N-type conductive element has an enriched region in the doped polysilicon layer, the enriched region is located on a side of the doped polysilicon layer away from the dielectric layer, and the N-type conductive element in the enriched region includes the oxide, which is a phosphorus oxide compound.
3. The passivation contact structure according to claim 1, characterized in that: The atomic percentage of the N-type conductive element in the doped polysilicon layer is 5% to 25%.
4. The passivation contact structure according to any one of claims 1 to 3, characterized in that: The surface doping concentration of the doped polysilicon layer is 2×10 20 cm -2 ~8×10 20 cm -2 The junction depth is 0.05μm~0.16μm, and the square resistance is 30Ω / sq~90Ω / sq.
5. The passivation contact structure according to claim 1, characterized in that: The thickness of the dielectric layer is 1 nm to 3 nm; and / or, The thickness of the doped polysilicon layer is 100nm-120nm.
6. A method for preparing a passivation contact structure according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Providing a silicon substrate, wherein the dielectric layer and the doped amorphous silicon layer doped with the N-type conductive element are sequentially arranged on the surface of the silicon substrate from the inside to the outside; Firstly, introducing an oxygen-containing gas into the doped amorphous silicon layer, and then depositing an oxygen-containing layer; Annealing is performed to transform the doped amorphous silicon layer into the doped polysilicon layer, and the oxygen-containing gas, the oxygen element in the oxygen-containing layer and the N-type conductive element are combined to form the oxide to inhibit the N-type conductive element in the doped polysilicon layer from diffusing toward the dielectric layer.
7. The preparation method according to claim 6, characterized in that: The amount of oxygen-containing gas introduced is greater than or equal to 1000 sccm.
8. The preparation method according to claim 6, characterized in that: The thickness of the oxygen-containing layer is 0.5 nm to 50 nm.
9. The preparation method according to claim 6, characterized in that: The oxygen-containing gas is deposited by a plasma enhanced chemical vapor deposition process, wherein the oxygen-containing gas comprises at least one of N2O and O2; and / or, The oxygen-containing layer is deposited by the plasma enhanced chemical vapor deposition process, and the deposited gas includes SiH4 and the oxygen-containing gas.
10. The preparation method according to claim 6, characterized in that: The dielectric layer is deposited by plasma enhanced chemical vapor deposition process, the deposition temperature is 400° C. to 500° C., and the deposition gas includes the oxygen-containing gas and inert gas.
11. The preparation method according to claim 6, characterized in that: The step of depositing the doped amorphous silicon layer comprises first depositing a hydrogenated intrinsic silicon layer and then depositing a doped layer, wherein the mass content of hydrogen in the intrinsic silicon layer is 10% to 20%.
12. The preparation method according to claim 11, characterized in that: The intrinsic silicon layer is deposited by plasma enhanced chemical vapor deposition at a temperature of 400° C. to 500° C., and the deposition gas includes SiH4 and H2; The doping layer is deposited by plasma enhanced chemical vapor deposition, and the deposited gas includes SiH4, a gas containing an N-type conductive element, and H2. The gas source flow rate of the gas containing the N-type conductive element is greater than 400 sccm.
13. The preparation method according to claim 11, characterized in that: The junction depth of the doping layer is 0.01 μm to 0.1 μm.
14. The preparation method according to claim 11, characterized in that: The thickness of the intrinsic silicon layer is 30nm to 40nm, and / or, The thickness of the doping layer is 70nm-80nm.
15. The preparation method according to claim 6, characterized in that: In the annealing process, the annealing temperature is 900°C to 950°C.
16. A solar cell, characterized in that: include: The passivation contact structure according to any one of claims 1 to 5 or the passivation contact structure prepared by the preparation method according to any one of claims 6 to 15.
17. A photovoltaic module, characterized in that: include: The passivation contact structure according to any one of claims 1 to 5 or the passivation contact structure prepared by the preparation method according to any one of claims 6 to 15.
Citation Information
Patent Citations
Method of employing ion implantation to prepare ultra low surface doping concentration low sheet resistance silicon solar cell
CN103811582A
Solar cell and preparation method thereof
CN116093180A
Front wide-band-gap doped combined passivation back contact solar cell and preparation method thereof
CN116525708A
Back selective doping passivation contact solar cell and preparation method thereof
CN117293195A
Solar cell, preparation method of solar cell and photovoltaic module
CN117293218A